Minimally Invasive Bariatric Surgery - Schauer, Phillip R.; Schirmer, Bruce D.; Brethauer, Stacy (Springer New York : Imprint: Springer, 2007)
"Minimally Invasive Bariatric Surgery" covers the full spectrum of laparoscopic weight loss surgery and the pathophysiology of obesity. The chapter authors, all currently operating experts in the field, cover the essentials of establishing a bariatric surgery program, including equipment needs, guidelines for training, and patient selection. The operative chapters discuss in full detail the surgical techniques and outcomes, including laparoscopic VGB, laparoscopic adjustable gastric banding, laparoscopic Roux-en-Y, and laparoscopic malabsorption procedures. The text also tackles post-operative issues, such as complications, reoperation, plastic surgery after weight loss, nutritional issues, and pregnancy following obesity surgery. The text is graphically enhanced with over 175 full-color and 265 black and white images: surgical photos, anatomical drawings, operative technique illustrations and management algorithms. "Minimally Invasive Bariatric Surgery" enables clinicians to provide their patients with a viable solution to chronic obesity.